Voluntary compensation of GHG emissions: Selection criteria and implications for the international climate policy system - Sonja Butzengeiger (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2005)
Legal entities or persons might want to neutralize the greenhouse gas emissions they have caused with their activities. In the context of this paper, voluntary compensation is defined as the cancellation of emission reduction credits that have been generated in a project-based approach. The question 'Which compensation project should be selected?', which is one of the central aspects of analysis, is a classic example of decision theory from the perspective of the compensating entity.
Keywords: 330